Analisis Faktor Penyebab Kesulitan Membaca Pada Siswa Kelas 5A SDN 060874 Medan Perjuangan - Nasution, Anggita Siva Liana; Harmila, Dina; Siregar, Dina Maimunah HS; Lainatussifa, Lainatussifa (CV. Lenggogeni Data Publishing, 2024)
The purpose of this study was to determine the factors that cause reading difficulties in high school students. The type of research is descriptive qualitative research. The data collection technique is by using interview techniques. The subjects used in this study were teachers in class V. Based on the results of the study, it can be concluded that the factors that influence students' reading difficulties are influenced by the students themselves (internal) and there are also influences that come from outside the students (external). The internal factors are the student's lack of interest in reading, the student is difficult to teach and often does not go to school. External factors are the lack of support or the role of parents and the influence of online learning during the Covid-19 pandemic which requires students to study at home with minimal direct interaction with teachers, which results in a lack of stimulation and assistance in the reading learning process.